PEMBAGIAN HARTA GONO GINI AKIBAT PERCERAIAN PERSPEKTIF HUKUM ISLAM - Abd. Basit Misbachul Fitri; Anggi Widiyastuti; Siti Fatimah; Sandi Ferdy Yulianto (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
This study examines harta gono gini (joint marital property) as shared assets acquired during marriage, analyzed through the Islamic legal concept of syirkah (partnership). The research explores how joint property is formed through spousal collaboration in livelihood, despite differing roles, and how it should be divided post-divorce to ensure fairness. Using a qualitative approach, this study analyzes religious and customary perspectives on asset distribution, emphasizing equity and local traditions (urf). Findings indicate that harta gono gini includes assets jointly earned during marriage, while individually acquired or inherited property remains separate. The study concludes that Islamic principles and socio-cultural norms must be balanced to achieve just solutions in marital property disputes.